Modern Applications in Optics and Photonics: From Sensing and Analytics to Communication - Alwis, Lourdes S. M.; Bremer, Kort; Roth, Bernhard Wilhelm (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Optics and photonics are among the key technologies of the 21st century, and offer potential for novel applications in areas such as sensing and spectroscopy, analytics, monitoring, biomedical imaging/diagnostics, and optical communication technology. The high degree of control over light fields, together with the capabilities of modern processing and integration technology, enables new optical measurement systems with enhanced functionality and sensitivity. They are attractive for a range of applications that were previously inaccessible. This Special Issue aims to provide an overview of some of the most advanced application areas in optics and photonics and indicate the broad potential for the future.